Analisis Penerapan Prinsip Bagi Hasil dan Manajemen Risiko pada Pembiayaan Musyarakah : Studi Kasus : Bank BNI Syariah Cabang Jambi - Sintia Eka Putri; Muhammad Subhan (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This study aims to determine how the process of implementing the principle of profit sharing and risk management in musyarakah financing at BNI Syariah Jambi branch. This study uses a qualitative research method with a field approach through structured interviews. The results of this study indicate that BNI Syariah Jambi branch in implementing the principle of profit sharing and risk management is in accordance with the procedures and provisions that have been set. Operational constraints of BNI Syariah in implementing the principle of profit sharing and risk. Customer income is not reported to the Bank every month. The level of customer honesty is very low in terms of business development.